Dispersion of linear and nonlinear optical susceptibilities and the hyperpolarizability of 3-methyl-4-phenyl-5-(2-pyridyl)-1,2,4-triazole - Ali Hussain, Reshak; Stys, D.; Auluck, S.; Kityk, I. V. (Royal Society of Chemistry (RSC) Publishing, 2011)
Link to publisher's homepage at http://pubs.rsc.org/